Effect of draw ratio on fiber structure development of polyethylene terephthalate. (5th May 2017) - Tomisawa, R.; Ikaga, T.; Kim, K.H.; Ohkoshi, Y.; Okada, K.; Masunaga, H.; Kanaya, T.; Masuda, M.; Maeda, Y.
Abstract: Fiber properties are decided by its structure, and the structure are mainly formed in the fiber drawing process. In this study, the effects of the draw ratio on the fiber structure development of polyethylene terephthalate after continuous neck-drawing were investigated using simultaneous WAXD/SAXS measurements. Low-oriented amorphous as-spun fibers were drawn to a draw ratio of 3.0–4.5, at which the fiber can be stably neck drawn. WAXD and SAXS images were obtained up to 2.0 ms when the structure was mainly developed. The smectic (001′) diffraction intensity and long period increased with increasing draw ratio up to 4.2, and a larger (001′) diffraction d -spacing was observed at a draw ratio of 4.5. The results suggest that more fibrillar structures were formed with increasing draw ratio up to 4.2, and more constrained molecular bundles were formed at a draw ratio of 4.5. A larger amount of constrained fibrillar structures can bear a greater tensile force in tensile tests, therefore the drawn fibers have higher tensile strengths. Graphical abstract: Highlights: Draw ratio dependence of fiber structure development was analyzed by WAXD/SAXS. No smectic phase, but an X-pattern, was observed at minimum draw ratio. The amount of smectic phase increased with drawing stress up to 100 MPa. The smectic phase d -spacing increased with drawing stress over 100 MPa. Tensile strength of drawn fiber increased with smectic phase amount and d -spacing.